Familial adenomatous polyposis: age of onset and association with mutations of the APC gene in patients from West Ukraine - Lozynska, M.R.; Lozynskyy, Y.S.; Plawski, A.; Pinyazhko, R.O.; Prokopchuk, N.M.; Fedota, O.M. (Вiopolymers and Cell, 2017)
Aim. To evaluate the average age of familial adenomatous polyposis (FAP) onset in both males, females and in their relatives, carriers or not carriers of the APC gene mutations, to estimate the anticipation in successive generations for early identification of the individuals in the risk group. Methods. The medical records, genealogical information were gathered and molecular genetic study of blood was carried out in 25 probands with adenomatous polyposis. FAP was confirmed in 44.0 % of probands. The probands with FAP had 36 affected relatives. The amplified frag-ments of the APC gene were screened for the mutations involving heteroduplex analysis and detection of single-stranded conformational polymorphism. The age of FAP onset was evaluated in probands and their relatives. The anticipation index (A) was calculated. Results. Among patients with FAP 61.7 % were males and 38.3 % were females. The age of FAP onset in males was 36.0 ± 1.4 years, while in females the disease manifested earlier – in 29.5 ± 2.4 years (p<0.01). The APC mutations, including four novel mutations, were found in 63.6 % of probands with FAP. The lowest age of polyposis onset was observed in carriers of the APC mutation c.3927_3931delAAAGA p.Q1309fs. The average age difference between FAP onset in the parents and their offspring was 12.0 ± 1.7 years. In 3 of 4 families with FAP and novel mutations of the APC gene predominance of males (12:4) and anticipation phenomenon were observed.The strongest age correlations of FAP onset were found in mother-offspring pairs and parents-son pairs. The statistically significant difference between the data confirmed more similarities of descendant, especially sons, with parents. Conclusions. There was no statistically significant differ-ence between average age of the disease onset in patients carriers of the APC mutations (33.1 ± 2.1 years) and in patients without the APC mutations studied by the traditional methods (33.7 ± 1.6 years). In offsprings with FAP the reduced age of disease onset compared to the parents was revealed irrespective of the presense of the APC mutations. The anticipation index in FAP was 18.0 %. Accounting anticipation allows estimating the approximate average age at FAP onset during genetic counseling, and therefore timely carries out targeted prevention.